Kecenderungan Bullying Pada Siswa Sekolah Menengah Pertama - Shinta V Pertiwi; Fuad Nashori (JURNAL PSIKOLOGI, 2011)
The purpose of this study is to examine the relationship between spiritual intelligence  and bullying tendency. The hypothesis submitted that there was negative relationship between spiritual intelligence  and bullying tendency in Nngaglik 1 Junior high school students. The higher spiritual intelligence correlated with lower bullying tendency and opposite. The subject on this study is 117 students grade 1 and 2 Ngaglik 1 Junior high school. Their age range from 10 to 14 years old. Data were collected by two scale, there are spiritual intelligence modified by Ikasari (2002) based on Zohar and Marshall (2000)  and bullying tendency scale modified by Rigby (Fleming, 2002). Method of correlation with SPSS 19 for windows. The result shoed that there was a significany relationship between spiritual intelligence  and bullying tendency (r=-0,472 with p =0.000(p,0,01>. This shows that higher  spiritual intelligence correlated with lower bullying tendency. The spiritual intelligence contribute as much as 22,3%.